INTERGENERATIONAL RELATIONS AND CHARACTERISTICS IN WESTERN EDUCATION (TAMADDUN NURI JURNALI, 2024)
The article is devoted to the study of the views of the family as a social institution, and the theories of the Western representatives on intergenerational relations in the family are presented. The purpose of the article is based on the collection and generalization of theories about the family. The conducted studies show that the family develops and changes along with the development of human society, it is its main component. The family is a part of society, which reflects all the changes that society has experienced, from the primitive family groups to the modern family. Such changes were of great interest to philosophers and became the basis for the origin of their theories about the family.